Pengabdian Masyarakat Tentang: Tatacara Meminta Layanan Visum Kepada Dokter - Purnama, Ade Sinta; Fauzan, Abdul (Universitas Malahayati, 2024)
Abstract: introduction: According to WHO in 2021, domestic violence is a problem that has very deep roots and occurs in all countries in the world. Domestic violence in America shows that every 9 minutes a woman becomes a victim of physical violence, and 25% of women are killed by their male partner. Formulation of the problem: Based on the background above, there are still many problems with victims who are suspected of having elements of a crime, so counseling is needed to the public about procedures for requesting visum et repertum services to doctors. Method: preparation and counseling activities. Results and discussion: polyclinic patients at one of the hospitals in the city of Bandar Lampung know how to request a post mortem et repertum service to a doctor. Conclusion: this is the patient and the patient's family regarding the procedure for requesting post mortem et repertum services to doctors to increase. Suggestion: The general public, especially polyclinic patients at one of the Bandar Lampung city hospitals, are getting more agile (immediately reporting) in asking for visum et repertum services to doctors if they experience criminal acts of violence.Keywords: victim, visum et repertum Abstrak: pendahuluan: Menurut WHO tahun 2021, kekerasan dalam rumah tangga merupakan permasalahan yang telah mengakar sangat dalam dan terjadi di seluruh negara di dunia. KDRT di Amerika menunjukkan setiap 9 menit perempuan menjadi korban kekerasan fisik, dan 25% perempuan yang terbunuh oleh pasangan laki-lakinya. Rumusan masalah: Berdasarkan latar belakang diatas masih banyak dijumpai permasalahan kepada korban yang dicurigai mengalami unsur tindak pidana sehingga diperlukan penyuluhan kepada masyarakat tentang tatacara meminta pelayanan visum et repertum kepada dokter. Metode: persiapan dan kegiatan penyuluhan. Hasil dan pembahasan: pasien poli pada salah satu rumah sakit di kota bandar lampung mengetahui bagaimana tatacara meminta pelayanan visum et repertum ke dokter. Kesimpulan: ini pasien dan keluarga pasien tentang tata cara meminta pelayanan visum et repertum kepada dokter meningkat. Saran: Masyarakat umum khusus pasien poli salah satu rumah sakit kota bandar lampung semakin cekatan (segera melaporkan) dalam untuk meminta layanan visum et repertum kepada dokter apabila mengalami tindak kekerasan tindak pidana. Kata kunci: tindak pidana, visum et repertum